The Warm House of Novgorodian Archbishop: The Heating System of the Vladychny (Faceted) Palace (1433) - Antipov, Ilya V.; Yakovlev, Dmitriy E. (Actual Problems of Theory and History of Art, 2019)
In 1433 Archbishop Evfimii II commissioned the construction of a new stone building in the Archbishop’s Yard in Novgorod. This year German masters erected so-called Vladychny (Faceted) Palace, a complex which consists of three parts. The main part of this building has survived, in 2012 the research and restoration works on the monument were completed. There are rooms for different purposes (residential,economic etc.) in the structure of the building. Most halls and passageways of the palace were not heated, but some rooms had a heating system.In total, there were three furnaces in the Vladychny (Faceted) Palace, which respectively heated three or four rooms. The furnaces had the same design, only the furnace in the north-western part of the chamber was somewhat different, since it was not placed on a vaulted base, like the rest of the furnaces, but directly on the boulder foundation. Heating worked on the principle of a hypocaust system: before the start of the heating the openings that went into the room were covered with lids. At the first stage the boulders situated on the vault were heated. Then after burning wood and removing smoke, the chimney was blocked, and the holes above the boulders, on the contrary, opened. The hot air from the boulders heated the hall.The hypocaust system of the Faceted Palace existed till the 16th century, when its elements gradually began to be replaced by conventional furnaces; in the 17th century tiled stoves appeared there.The hypocaust heating system in the 13th–15th centuries was widespread in residential and public buildings, castles of the Baltic region. Before the construction of the Faceted Palace, this type of heating was not apparently used in Old Russia.The presence of furnaces under some halls allows us to approach the understanding of the purpose of certain premises of the building, and, accordingly, to understand more clearly the diversity of its functions, as well as to reveal some features of the building façade solution that appeared due to the construction of furnaces.
Keywords: Old Russian architecture; Novgorod the Great; stone civil buildings; heating system; architecture of brick Gothic